New approaches to spatial planning and design. Planning, design, applications. - (:unkn) unknown (Lang, 2019)
One of the main objectives of planning and design is the reflection of the works to the space. Therefore, the starting point of this book is to reveal the research conducted by different professions in the field of spatial planning and design. For this purpose, original researches on direct application and land were included. Planning and design studies need co-operation between professions in order to fulfill this philosophy. These activities are effective means of fulfilling the philosophy of sustainability. Planning and design is a tool to tell the story of a community, and how it s past, present and future work together for a sustainable tomorrow. The design process in which the most appropriate spatial compositions are revealed by shaping the areas in the direction of planning decisions, develops in the continuation of the planning process. This book is for landscape architects and other planning and design professions. Theoretical foundations, theories, methods, and applications will be essential parts of this reference book. In addition, this book addresses several very different subjects of study; landscape management, biodiversity, landscape restoration, landscape design, urban design, urban planning and architectural design related to theory, practice and the results will be covered.
Keywords: Raumplanung; Regionalplanung; Stadtplanung; Smart City; Digitalisierung; Großstadt; Governance; Fußgängerverkehr; Stadtgestaltung; Stadtökologie; Grünraum; Fremdenverkehr; Dorf; Ländlicher Raum; Nachhaltige Entwicklung; Stadtsoziologie; Hochschulplanung; Kulturelle Identität